2016
DOI: 10.1007/s11010-016-2658-5
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells

Abstract: Cardiovascular disease is a growing major global public health problem. Oxidative stress is regarded as one of the key regulators of pathological physiology, which eventually leads to cardiovascular disease. However, mechanisms by which FGF-2 rescues cells from oxidative stress damage in cardiovascular disease is not fully elucidated. Herein this study was designed to investigate the protective effects of FGF-2 in H2O2-induced apoptosis of H9c2 cardiomyocytes, as well as the possible signaling pathway involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Several studies suggest that the protective effects of FGF-2 are mediated by PKC and MAPK activation [27]. Moreover, the PI3K/AKT pathway, which is independent of the PKC, PKA, and MAPK signaling pathways [28,29], is activated by FGF-2 and prevents ROS-induced apoptosis in H9c2 cells through the Forkhead box O3 (FoxO3a) transcription factor [30]. The FoxO3a transcription factor is one of the most important downstream targets of PI3K/Akt signaling and a crucial regulator of apoptosis [18,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that the protective effects of FGF-2 are mediated by PKC and MAPK activation [27]. Moreover, the PI3K/AKT pathway, which is independent of the PKC, PKA, and MAPK signaling pathways [28,29], is activated by FGF-2 and prevents ROS-induced apoptosis in H9c2 cells through the Forkhead box O3 (FoxO3a) transcription factor [30]. The FoxO3a transcription factor is one of the most important downstream targets of PI3K/Akt signaling and a crucial regulator of apoptosis [18,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been known that Phosphoinositide 3‐kinase (PI3K)‐Akt pathway is also associated with FGF signal and Sprouty2 in cell proliferation and survival (Ornitz and Itoh, ; Zhang et al, ; Liu et al, ). Therefore, to examine the influence of Sprouty2 on PI3K‐Akt pathway in MC3T3‐E1 cells, we investigated the phosphorylation of Akt in the same way as for ERK1/2 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Statistically significant differences were determined by the Mann-Whitney U-test ( * P < 0.05). (Ornitz and Itoh, 2015;Zhang et al, 2015;Liu et al, 2016). Therefore, to examine the influence of Sprouty2 on PI3K-Akt pathway in MC3T3-E1 cells, we investigated the phosphorylation of Akt in the same way as for ERK1/2 phosphorylation.…”
Section: Figurementioning
confidence: 99%
“…Here, we focus on the PI3k/Akt/FoxO3a pathway, which plays crucial role in promoting survival and function of cardiomyocyte. The previous studies have shown that hydrogen peroxide induces cardiomyocyte apoptosis by inhibiting the PI3K/Akt pathway . The PI3K/Akt pathway has shown related to the human atherosclerosis .…”
Section: Discussionmentioning
confidence: 98%
“…The previous studies have shown that hydrogen peroxide induces cardiomyocyte apoptosis by inhibiting the PI3K/Akt pathway. 33 The PI3K/Akt pathway has shown related to the human atherosclerosis. 34 FoxO3a is an important downstream target of the PI3K/Akt pathway, which was mainly regulated by Akt.…”
Section: Discussionmentioning
confidence: 99%